Finite element modeling and analysis of a debonded smart beam in actuation - Butt, Mohammad Mursaleen; Ahmad, Sheikh Nazir; Al-Robian, Abdulrehman A; Khan, Sher Afghan (Blue Eyes Intelligence Engineering & Sciences, 2019)
Stress, strain and displacement-based analysis of smart beam with debonding under actuation have been carried out. In this regard variational formulation based finite element modeling of a smart beam under actuation with debonding on the top and a bottom piezo layer has been developed. To know the proper functioning of the model, debonding at the center of the span and one-third of the span at the top and bottom interfaces between core and the piezo patches has been considered. Higher-order beam bending for both host and piezo layers has been incorporated in the model. Due to debonding the number of degrees of freedom increase according to the number of elements considered along debonding portion. It can be observed that the results exhibit symmetry about the centroidal axis which guarantees that the finite element model functions satisfactorily. Electric field along longitudinal and transverse directions does not change with regards to bonding and debonding in actuation. The pattern of axial displacement, normal strain, and normal stress through-thickness along span is found to be not affected by the debonding in actuation which is contrary to sense. Which means the smart beam with debonding does not degenerate in actuation for axial displacement, normal stress, and normal strain. The magnitudes of shear stress and shear strain at the root are minimum as compared to the magnitudes at the tip of the smart cantilever. However, the difference between bonding and debonding with regards to shear stress and shear strain is predominant at the root than at the tip. Which means the smart beam does not degenerate in debonding with regards to shear strain and shear stress.